ANALISIS PERILAKU KONSUMSI MASYARAKAT DAYAK LEBANG DI DESA PENGKADAN BARU KECAMATAN DEDAI KABUPATEN SINTANG - Darmawan, Irfansius Roni; Mashudi, Mashudi; Basri, Muhammad (Universitas Tanjungpura, 2023)
This study aims to determine the consumption behavior of the Dayak Lebang community in Pengkadan Baru Village, Dedai District, Sintang District. The approach used is in the form of qualitative research with the type of case study research. The data source in this study is the Dayak Lebang community, which consists of 10 people. Methods of data collection is done by interviews and documentation. The results showed that the consumption behavior of the Dayak Lebang community in Pengkadan Baru Village leads to rational behavior by considering beliefs to act as a response to whether an object (attitude) is good or not in the actions taken, by determining initial planning, buying consumer goods and determining consumption patterns with a long term. time based on circumstances. Communities consider beliefs from surrounding views about an object (subjective norms) for actions taken, by making purchasing decisions for consumer goods based on input from the closest people, determining views in consuming with other people's input based on circumstances, choosing input from the closest people in carrying out consumption activities and determine beliefs about consumption activities carried out from the pressure of the people around them. Society uses the basis of perceptions about the ease or difficulty of realizing a behavior (behavioral control) from the actions taken, by determining reasons, controlling limitations and determining impacts in carrying out consumption activities